Tadris al-Fiqh al-Islami wa Usulihi fi al-Jami’at wifqa li Istirajiyyat Tarbawiyyah Hadithah (( al-Khara`it al-Mufahamah Anamuzijan )) - Hammad, Hamzah Abd al-Karim (Jurnal Fiqh, 2009)
Dictation teaching technique is considered as one of the most standout teaching techniques, which is used nowadays to teach Islamic jurisprudence and its principles that affects declining learner`s thinking level as well as predominance of traditional style. The study tries to provide new teaching methods, in basis of conception maps; therefore, the study is seeking to breakdown a ring around the teaching curriculums. The methodology is followed in this study is firstly the description method of conception maps theoretical background, then converted to the applied experimental method in designing conception maps for various aspects of Islamic jurisprudence and its principle. The research concluded to the importance of applying modern education theories in the Islamic science fields especially, jurisprudence and its principles. The study recommended applying this strategy on all other fields of Islamic studies.